Accountability one step removed - Axel Sonntag; Daniel John Zizzo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In a repeated real effort team production experiment workers receive a distorted signal about their co-players' previous efforts. We vary the degree to which production can be directly traced back to a participant's real or randomly drawn effort level. We find that individuals produce much less and the decline of contributions over time is significantly steeper under high as compared to low accountability. In an additional endogenous accountability condition observe the highest effort level.
Keywords: C91; D82; M54; 330